Blackleg and Soft Rot of potatoes : Two decades of research and developments in Finland - Degefu, Yeshitila (Luonnonvarakeskus, 2024)
Potato is the third food crop after rice and wheat in the world, recommended by the United Nations (FAO) as the global food security crop. Despite such high promises, potato suffers from production constraints which result in reduced yield and quality of harvest. Diseases are among the most crucial factors in the potato production. Potato is attacked by about 160 diseases and disorders which are fungal, bacterial, and viral origin and many other unknown causes. Late Blight caused by the Oomycete Phytophthora infestans, the most devastating disease that led to the infamous Irish Famine in the mid19th century (1845-1850), is remembered as one of the tragic events in human history and the unsolved problem of Plant Pathology in the 21st century. Blackleg and soft rot of potatoes are diseases caused by the bacteria in the genera Dickeya and Pectobacterium are very destructive diseases which are consistent threats to potato production in the world. The bacteria are among the top ten bacteria in economic importance. This report is a brief highlight of a two-decade research advances about these pathogens in the Natural Resources Institute Finland (Luke) and the former Agrifood Research Finland (MTT). It covers major outcomes and achievements in molecular diagnostics (method developments, standardization for research and end user applications), monitoring and surveillance of Dickeya and Pectobacterium aimed at safeguarding the EU granted High-Grade status of Finland for seed potato production and some remarks and recommendations for the management of emerging and re-emerging species to support policy formulation and effective blackleg disease management strategies in Finland. Information and knowledge generated during the last twenty years have been published in international scientific journals and professional Newsletters and disseminated to stakeholders in the potato value chain for awareness and active engagement in disease control. The report does not include descriptions of methodological protocols due to space limitations but interested readers could refer to our relevant publications listed in the reference section of this report where the experimental procedures are described in detail. The report is a useful reference document for young researchers who would like to know about blackleg and blackleg research in Finland- current status and future prospects and build projects to tackle the many potential challenges posed by blackleg to Finnish and global food security. Furthermore, the report is a brief synthesis of selected topics presented in a form simple to understand not only to experts in Plant Pathology but also to those who are involved in formulation of Phytosanitory policy guidelines or decision makong.
Keywords: potato; black leg (plant diseases); soft rot (plant diseases); molecular diagnostics; high-grade status; dickeya spp.; pectobacterium spp.